2006
DOI: 10.1007/s00198-005-0028-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural effects of raloxifene on the proximal femur: results from the multiple outcomes of raloxifene evaluation trial

Abstract: We conclude that raloxifene does not influence periosteal apposition in the proximal femur but it nevertheless produces small but significant improvement in resistance to axial and bending stresses (CSA and SM, respectively) at all analyzed regions. The significant reductions in buckling ratio suggest that additional strength loss due to cortical instability is also ameliorated by treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 25 publications
1
22
1
1
Order By: Relevance
“…However, BMD at those sites showed a tendency to increase to some extent, although not statistically significant, suggesting that the tendency might reach significance in longer observation or larger number of subjects. Additionally, there is increasing evidence that the effects of RLX to reduce the risk of fractures hardly depend on the increase of BMD [17][18][19]. Therefore, we do not think that our findings of no increase of BMD at the non-vertebral sites rule out the potential effects of RLX to reduce the risk of non-vertebral fractures.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…However, BMD at those sites showed a tendency to increase to some extent, although not statistically significant, suggesting that the tendency might reach significance in longer observation or larger number of subjects. Additionally, there is increasing evidence that the effects of RLX to reduce the risk of fractures hardly depend on the increase of BMD [17][18][19]. Therefore, we do not think that our findings of no increase of BMD at the non-vertebral sites rule out the potential effects of RLX to reduce the risk of non-vertebral fractures.…”
Section: Discussioncontrasting
confidence: 53%
“…A large-scale double-blinded prospective randomized study to evaluate its effects on prevention of fractures, vertebral or non-vertebral, is warranted for Japanese postmenopausal women. Recent data from RLX trials have demonstrated that RLX reduces the relative risk of incident vertebral fractures to a level comparable to that observed with bisphosphonates [1, [17][18][19], although RLX induces smaller increase in BMD compared with bisphosphonates [16]. Therefore, RLX has been considered to exert its beneficial effects on bone not by increasing BMD as mentioned above, but rather mainly by improving 'bone quality', [17,18,22] indicating bone turnover markers as one of the best ways to estimate the therapeutic effects of RLX on bone at a clinical level [18,22,23].…”
Section: Discussionmentioning
confidence: 98%
“…The cross-sectional indices we studied are applicable only to a plane of a DXA image. However, proximal hip geometry obtained by the above method is widely used to understand femoral structure and strength [56,57] and has been shown to predict osteoporotic fragility in several epidemiological studies [8,58,59]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies investigating the effect of HRT [22], raloxifene [31], or the combination of HRT and alendronate [23] on HSA have not reported this discrepancy, which might be explained by the fact that these studies included women age 65 and older. We recruited a younger, newly postmenopausal population, mean age 50, whose skeleton might be more resilient to negative impact.…”
Section: Discussionmentioning
confidence: 88%
“…Investigators reported that raloxifene resulted in improved conventional hip BMD and was associated with improvement of bone CSA, section moduli, and buckling ratios over 3 years as assessed by Beck's HSA analysis [31]. Raloxifene did not affect periosteal apposition, but produced minimal significant increases in cross sectional areas and section moduli.…”
Section: Discussionmentioning
confidence: 99%